Ligação entre as propriedades estruturais, ópticas, eletrônicas e atividade fotocatalítica de Ag3PO4:Mo - Trench, Aline Barrios (2018)
Silver phosphate (Ag3PO4) has received considerable attention from the scientific community due to photocatalytic and photoluminescent properties. However, some alternatives were sought to improve the performance of these properties by material modification, metal deposition, doping cation or anion or coupling with another semiconductor. In this sense, the objective of this study was the evaluation of the semiconductor Ag3(P1-xMox)O4 where Mo6+ was inserted in the crystalline structure in the form of doping. This process consists in the insertion of impurities in the structure of the solid at specific positions of the crystalline reticulum replacing the original structural units. It was also the objective of this study to synthesize the desired materials by chemical precipitation in aqueous medium and to relate the influence of the dopant on the structural, morphological, photoluminescent and photocatalytic properties together with theoretical calculations. The characterization of the samples was made by X-ray diffraction (XRD), ultraviolet-visible (UV-Vis) absorption spectroscopy, X-ray photoelectron spectroscopy, Raman spectroscopy, scanning electron microscopy (SEM), microscopy transmission electron microscopy (TEM), photoluminescence spectroscopy (PL) and theoretical calculations based on the Density Functional Theory. Photocatalytic tests were done for degradation of Rhodamine B under visible light irradiation. The samples with doping less than 2% did not present a second phase, demonstrating an effective doping, and changes in photoluminescence and band gap values showed that doping caused defects in the structure of the material, and these defects contributed to the photocatalytic improvement of the doped materials in comparison with pure material, the material being doped with 0.5% of Mo, which presented better results for degradation of Rhodamine B.